Incidence and prevalence of psychogenic nonepileptic seizures in a Norwegian county: A 10‐year population‐based study. (2nd June 2021) - Villagrán, Antonia; Eldøen, Guttorm; Duncan, Roderick; Aaberg, Kari Modalsli; Hofoss, Dag; Lossius, Morten Ingvar
Abstract: Objective: This study was undertaken to measure the incidence and prevalence of active psychogenic nonepileptic seizures (PNES) in a Norwegian county. Methods: Using the Norwegian patient registry, we identified patients in Møre and Romsdal County in Norway diagnosed with F44.5 (conversion disorder with seizures or convulsions) or R56.8 (convulsions, not elsewhere classified) in the period January 2010 to January 2020. A review of the patients' medical records and an assessment of diagnostic validity were performed. PNES were diagnosed according to the recommendations by the International League Against Epilepsy Nonepileptic Seizures Task Force. Point prevalence of PNES on January 1, 2020 and incidence rates for the period 2010–2019 were determined. Results: Based on PNES within the past 5 years, we found a PNES prevalence of 23.8/100 000 (95% confidence interval [CI] = 17.9–29.6), including all levels of diagnostic certainty. For the highest level of diagnostic certainty (video‐electroencephalographically confirmed), the prevalence was 10.6/100 000 (95% CI = 6.7–14.5). The highest prevalence was found in the age group 15–19 years, at 59.5/100 000 (95% CI = 22.6–96.3). The mean annual incidence rate between 2010 and 2019 was 3.1/100 000/year (95% CI = 2.4–3.7). Significance: We report for the first time a population‐based estimate of the prevalence of PNES. Our findings suggest that the prevalence of PNES is within the range of estimates from non‐population‐based data. We found a strikingly high prevalence of PNES in the 15–19‐year age group.